European erotic Romance : philhellene Protestantism, renaissance translation and English literary politics - Skretkowicz, Victor (Manchester University Press, 2018)
European Erotic Romance examines the Renaissance publication and translation of the ancient Greek erotic romances, and English adaptations of the genre by Sir Philip Sidney, Shakespeare and Lady Mary Sidney Wroth. Providing fresh insight into the development of the novel, this study identifies the politicisation of erotic romance by the European philhellene (lovers of all things Greek) Protestant movement. To English translators and authors, the complex plots, well developed moralised characters (particularly female) and rhetorical styles of the ancient novels signify political and social reform. Generous quotation and translations ensure that European Erotic Romance is accessible to a broad spectrum of readers. Its organisation lends itself to use as a course text. It is suitable for use by senior undergraduates and specialists in Renaissance literature, translation, rhetoric and history.
Originally published in print form: 2010.
In-house editor: Matthew Frost.
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation.; Sidney, Philip, -- 1554-1586 -- Criticism and interpretation.; Wroth, Mary, -- Lady, -- approximately 1586-approximately 1640 -- Criticism and interpretation.; Wroth, Mary, -- Lady, -- approximately 1586-approximately 1640.; Sidney, Philip, -- 1554-1586.; Shakespeare, William, -- 1564-1616.; Romances, Byzantine -- History and criticism.; Romances, Byzantine -- Translations into English.; Romances, English -- History and criticism.; Roman courtois anglais -- Histoire et critique.; Literature and literary studies.; Literary studies: general -- Literary studies: c. 1500 to c. 1800.; LITERARY CRITICISM -- Ancient & Classical.; Romances, English.; Romances, Byzantine.; Biography, Literature & Literary studies -- Literature: history & criticism -- Literary studies: ancient, classical & medieval.; Electronic books; Translations.; Criticism, interpretation, etc.